Enhancing survival resonances with engineered dissipation - Shijie Chai; Mikkel F. Andersen (Physical Review Research, 2020)
We investigate a scheme that enhances survival resonances in a δ-killed system through actively recycling lost atoms. The process causes atoms to dissipate into superpositions of momentum states with sustained survival when exposed to kicks of a dissipative optical standing wave. The recycling process causes momentum redistribution, which gives the atoms multiple chances to enter a long-surviving mode. The survival resonance peak height shows an improvement of a factor of 2.4. This technique can increase the sensitivity and precision of atomic interferometers based on survival resonances.